Matriz energética brasileira à luz da economia verde: perspectiva política e jurídica - Girão, Mardônio da Silva (2015)
This thesis is a legal analysis of the Brazilian Energy Matrix vis-s-vis the principles of the Green Economy. It aims to investigate the existence of evidences that Brazil, as a signatory to the United Nations Framework Convention on Climate Change, is heading towards a green economy, and examines the possibilities to change the country¿s energy matrix considering public policies and domestic legislation with a focus on Green Economy. The main objective was to investigate whether the legal instruments of the Brazilian legislation promote or not the UNEP report entitled ""Towards a Green Economy: pathways to sustainable development and poverty eradication"". The guidelines and policies related to energy were evaluated as defined in the country, and their commitment towards sustainability and encouragement to the adoption of renewable energy sources. It was essential to analyze the Brazilian regulatory instruments in the light of the Green Economy proposal, in particular the recommendations of the UNEP report, maximum in terms of obligations. ""Greening"" the Brazilian energy sector will require efforts, ranging from replacement of carbon intensive energy sources to investments in clean energy, increments in the energy efficiency and advances in standardization in a broader aspect, especially the revision of the specific set of laws that ensures the regulatory compliance of the energy legal framework, in particular the National Energy Policy (PEN). The survey also helped to clarify the relationship between Green Economy and Sustainable Development as a contribution to the understanding of the UNEP report and its legal nature of soft law as a doctrine and a reference mark for behavior modification, consumption patterns and production. This assessment also identified on the UNEP report where to focus legislation and where to change. The methodology used was a survey and analysis of official documents and data, international treaties and agreements in the area of Green Economy, of relevant references as well as the main laws of Brazil, the incident and promotion legislation.